Identifying Environment Aspect in Academic Enhancement Support for Student-Athlete Using Fuzzy Delphi Method - Rozali, Mohd Zulfadli; Puteh, aifullizam; Yunus, Faizal Amin Nur; Azizuddin Khan, Thariq Khan (International Journal of Psychosocial Rehabilitation, 2020)
Student-athletes who are enrolled at the undergraduate level in higher educational institutions in Malaysia have the challenge of raising their academic achievement. Preliminary survey shows that nearly 40 percent of student-athletes have cumulative grade point average (CGPA) below 3.00. This study aimed to develop an academic enhancement support framework for student-athletes in Malaysian Public Universities. Problems, in order to improve academic achievement among student-athletes, are due to factors of environment that do not support the improvement of academic achievement student-athletes during their study sessions. As a result, student-athletes could not be maintained in the session of study, scholarship, and the implications from the result are they are not allowed to participate in training and also competition. Therefore, the purpose of this study was to identify elements of support enhance academic achievement to student-athletes in aspects of the environment. Qualitative research approach involves 12 respondents representing academia, management institutions and the management of student-athletes to explore elements of support enhance academic achievement in aspects of the environment for student-athletes. A total of 12 experts representing academia, management institutions and the management of student-athletes were selected to analyze the fuzziness consensus of experts. All collected data were analyzed using the fuzzy Delphi method. The result of the analysis found that there are 9 elements in aspects of the environment that fulfill the requirement consensus of experts, which threshold value is equal and less than 0.2, the percentage of the expert group is more than 75%. Therefore, 9 elements of support to help undergraduate student-athletes at public universities to improve their academic achievement.